2019
DOI: 10.1101/630822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput isolation and culture of human gut bacteria with droplet microfluidics

Abstract: 30Isolation and culture of gut bacteria enable testing for microbial roles in disease and 31 may also lead to novel therapeutics. However, the diversity of human gut microbial 32 communities (microbiota) impedes comprehensive experimental studies of individual 33 bacterial taxa. Here, we combine advances in droplet microfluidics and high-throughput 34 DNA sequencing to develop a platform for isolating and assaying microbiota members 35 in picoliter droplets (MicDrop). MicDrop can be used to create millions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…High-throughput anaerobic droplet cultivation has a significant potential to accelerate the study of gut bacteria and the isolation of presently uncultivated species. For instance, in parallel to our work here, Villa et al (2019) recently cultivated human stool microbes in droplets and screened carbohydrate utilization of bacteria from nine stool donors in order to determine the inter-individual variation in metabolic utilization [11]. Here, we demonstrated that our technology enabled an enrichment of low abundance organisms and reduced the variation of the cultivated taxonomic composition between media.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…High-throughput anaerobic droplet cultivation has a significant potential to accelerate the study of gut bacteria and the isolation of presently uncultivated species. For instance, in parallel to our work here, Villa et al (2019) recently cultivated human stool microbes in droplets and screened carbohydrate utilization of bacteria from nine stool donors in order to determine the inter-individual variation in metabolic utilization [11]. Here, we demonstrated that our technology enabled an enrichment of low abundance organisms and reduced the variation of the cultivated taxonomic composition between media.…”
Section: Discussionmentioning
confidence: 68%
“…However, some bacteria prefer defined media over rich media [12] while others utilize surface features such as hydrophobicity, roughness, and surface chemistry to form biofilms and proliferate [42]. Further enrichment of anaerobic organisms within our droplet platform could be achieved by incorporating droplet generation with defined media [11], combinatorially generated gradients of media [43], or varying the droplet surfactant chemistries to improve biofilm formation [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A complementary trend is the miniaturization of the culture vessels 12,14,[18][19][20][21][22][23][24][25][26][27][28][29][30] to save material and time while increasing the throughput and thereby the chance to find non-dormant, culturable variants of naturally occurring species. These microscale culture techniques have the idea in common to partition complex bacterial communities on the single cell level, allowing the various species to grow at their own speed, since they do not have to compete neither for space nor for nutrients.…”
Section: Introductionmentioning
confidence: 99%